Sandwich method to grow high quality AlN by MOCVD. (7th February 2018) - Demir, I; Li, H; Robin, Y; McClintock, R; Elagoz, S; Razeghi, M
Abstract: We report pulsed atomic layer epitaxy growth of a very high crystalline quality, thick ( 2 µ m) and crack-free AlN material on c -plane sapphire substrates via a sandwich method using metal organic chemical vapor deposition. This sandwich method involves the introduction of a relatively low temperature (1050 °C) 1500 nm thick AlN layer between two 250 nm thick AlN layers which are grown at higher temperature (1170 °C). The surface morphology and crystalline quality remarkably improve using this sandwich method. A 2 µ m thick AlN layer was realized with 33 arcsec and 136 arcsec full width at half maximum values for symmetric ( 0 0 0 2 ) and asymmetric ( 1 0 1 ̄ 5 ) reflections of ω -scan, respectively, and it has an atomic force microscopy root-mean-square surface roughness of 0.71 nm for a 5 × 5 µ m 2 surface area.